2009
DOI: 10.1109/tmi.2008.2010443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oblique X-ray Incidence in Flat-Panel Computed Tomography of the Breast

Abstract: Abstract-We quantify the variation in resolution due to anisotropy caused by oblique X-ray incidence in indirect flat-panel detectors for computed tomography breast imaging systems. We consider a geometry and detector type utilized in breast computed tomography (CT) systems currently being developed. Our methods rely on MANTIS, a combined X-ray, electron, and optical Monte Carlo transport open source code. The physics models are the most accurate available in general-purpose Monte Carlo packages in the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…1,2 In some cases, detector blur is ignored altogether. 3,4 However, recent studies [5][6][7] have demonstrated that there are large variations in the PRF across the detector face and that it can be highly asymmetric for large incidence angles. A recent study measured the MTF of an experimental benchtop tomosynthesis system with a flat panel indirect detector as used in a GE Senographe 2000D system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In some cases, detector blur is ignored altogether. 3,4 However, recent studies [5][6][7] have demonstrated that there are large variations in the PRF across the detector face and that it can be highly asymmetric for large incidence angles. A recent study measured the MTF of an experimental benchtop tomosynthesis system with a flat panel indirect detector as used in a GE Senographe 2000D system.…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, simulations were carried out for a breast CT system. 6 This system had a source-to-isocenter distance of 44 cm, a source-to-detector distance of 88 cm, and a 30ϫ 40 cm 2 detector with a 600 m thick phosphor screen, with x-ray energies of 30-70 keV. Increases in blur with respect to normal x-ray incidence were measured by performing a two-dimensional ͑2D͒ Gaussian fit to the PRFs and dividing the major axis of the fitted Gaussian with the major axis of the fitted Gaussian at zero degree incidence.…”
Section: Introductionmentioning
confidence: 99%
“…This is implemented with a roughness algorithm that was described in our previous papers. 5,14 However, the introduction of this variation in the geometry is not based at the moment on any physical characterization performed on actual screens. To be consistent with results presented in previous papers, we have used the same amount of variability ͑a = 0.2, where a is a user-adjustable parameter that defines the amount of mixing of the surface normal with an isotropic vector͒ as defined in Ref.…”
Section: Iva Accurate Knowledge Of Screen Detailsmentioning
confidence: 99%
“…It has already been applied to characterize breast tomosynthesis 13 and breast computed tomography ͑CT͒ systems. 14 Incorporation of the complete, anisotropic scintillator response has the potential to substantially improve system design and reconstruction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of DBT systems on the market or in development perform the tomosynthesis acquisition by scanning an x‐ray tube along an arc above a flat‐panel x‐ray detector, performing multiple exposures during the scan. With a fixed x‐ray detector, this scheme results in oblique incidence on the detector, which in turn results in varying detector response depending on the angle of incidence for each projection, as investigated by multiple groups . Controlled variation between projections can, however, also be beneficial to image quality; by appropriately varying the dose among the different projections, it is possible to enhance image quality for specific tasks …”
Section: Introductionmentioning
confidence: 99%